Reviewing the Business Case for Corporate Social Responsibility: New Evidence and Analysis - Schreck, Philipp 1978- (2011)
This study complements previous empirical research on the business case for corporate social responsibility (CSR) by employing hitherto unused data on corporate social performance (CSP) and proposing statistical analyses to account for bi-directional causality between social and financial performance. By allowing for differences in the importance of single components of CSP between industries, the data in this study overcome certain limitations of the databases used in earlier studies. The econometrics employed offer a rigorous way of addressing the problem of endogeneity due to simultaneous causality. Although the study’s results provide no evidence that there is a generic or universal business case for CSR, they indicate that there is a strong link between single stakeholder-related issues of CSR and financial performance. However, the analysis does not establish causality within these relationships.
Keywords: Causality; Empirical; CSP/CFP link; Corporate Social Performance; Corporate Social Responsibility; Business Case